QUALITY CONTROL ASSESSMENT OF FOUR BRANDS OF TINIDAZOLE TABLETS MARKETED WITHIN KADUNA METROPOLIS, KADUNA-NIGERIA - A. Muntaqa; A. Musa; M.A. Usman; A.Y. Idris; A. Olowo-Okere (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2018)
Introduction: Like most drugs, various brands of tinidazole tablets are available in Nigeria and therapeutically equivalent products are being selected for various reasons. This study aimed to investigate the quality control parameters of four commonly used tablet brands of tinidazole in Kaduna, Nigeria with a view to ascertain the quality and interchangeability of the different brands of the tablets. Four brands of tinidazole tablets sourced from the major pharmacies within Kaduna metropolis were identified, assayed and evaluated for uniformity of weight, friability, disintegration time, uniformity of dosage units and dissolution following standard BP (2009) procedures. The IR spectra and melting points (125-128°C) analysis of the four brands were within the normal compendium specified range. The brands passed the uniformity of weight and friability tests.Additionally, the absolute drug content of tinidazole in two of the four brands was however outside the specified range. Three (3) of the four (4) brands passed the disintegration tests within the disintegration time frame of less than 15 minutes. The four brands of tinidazole tablets marketed in Kaduna city vary in quality and so their use interchangeably should be carefully considered.